The Effect Of Marketing Mix, Brand Image, Halal Label, And Word Of Mouth On Syrup Purchase Decisions At Cafés In Surabaya - Kurniawan, Hans (Universitas Ciputra Surabaya, 2022)
This study aims to analyze the effect of the marketing mix, brand image, halal label, and word ofmouth on syrup purchasing decisions at cafes in Surabaya. By analyzing these factors, it is hoped that thecompany can determine the right strategy to increase sales. This study applied the quantitative researchmethod by distributing questionnaires as a data collection method. The sample in this study amounted to 52respondents using the convenience sampling technique. The results showed that product, price, promotion,distribution, and brand image had a significant effect on syrup purchasing decisions, while halal labels andword of mouth did not significantly affect syrup purchasing decisions at cafes in Surabaya. This relates tothe context of the research that respondents answered for products that they do not consume themselves,but products that are used in business processes or business procurement.